2024
DOI: 10.3390/medicina60040527
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence (AI) for Early Diagnosis of Retinal Diseases

Uday Pratap Singh Parmar,
Pier Luigi Surico,
Rohan Bir Singh
et al.

Abstract: Artificial intelligence (AI) has emerged as a transformative tool in the field of ophthalmology, revolutionizing disease diagnosis and management. This paper provides a comprehensive overview of AI applications in various retinal diseases, highlighting its potential to enhance screening efficiency, facilitate early diagnosis, and improve patient outcomes. Herein, we elucidate the fundamental concepts of AI, including machine learning (ML) and deep learning (DL), and their application in ophthalmology, undersco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…The incorporation of AI into automated retinal image analysis provides a valuable tool for expanding screening initiatives, enhancing diagnostic precision, and facilitating early intervention for a wide spectrum of retinal diseases. These AI-driven systems not only streamline disease detection processes but also have the potential to transform the diagnosis and management of eye diseases, ultimately leading to better patient outcomes and improved access to timely care [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…The incorporation of AI into automated retinal image analysis provides a valuable tool for expanding screening initiatives, enhancing diagnostic precision, and facilitating early intervention for a wide spectrum of retinal diseases. These AI-driven systems not only streamline disease detection processes but also have the potential to transform the diagnosis and management of eye diseases, ultimately leading to better patient outcomes and improved access to timely care [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…Population-based analysis indicated that 1 in 4000 individuals are affected by RP worldwide [ 5 ]. RP is characterized by significant variability among patients [ 6 , 7 , 8 ], with many exhibiting the classic symptoms such as impaired dark adaptation and night blindness during adolescence and loss of mid-peripheral visual field during young adulthood, both attributed to rod dysfunction [ 9 ]. As the disease progresses, patients suffer the loss of far peripheral vision, eventually developing tunnel vision, and ultimately experiencing the compromise of the central vision due to cone impairment in the later stages of life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond traditional prosthetics, cutting-edge research into electronic visual prostheses, often referred to as "bionic eyes", aims to restore sight through the direct stimulation of visual pathways in the brain or the remaining parts of the visual system[ 10 ]. These devices, which can include retinal implants and cortical visual prostheses, translate external visual information captured by cameras into electrical signals that the brain can interpret, offering a form of sight to those with certain types of blindness[ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%